Prebiotics as a modulator of gut microbiota in paediatric obesity. Issue 4 (13th April 2016) - Nicolucci, A.C.; Reimer, R.A.
Summary: This review highlights our current understanding of the role of gut microbiota in paediatric obesity and the potential role for dietary manipulation of the gut microbiota with prebiotics in managing paediatric obesity. The aetiology of obesity is multifactorial and is now known to include microbial dysbiosis in the gut. Prebiotics are non‐digestible carbohydrates which selectively modulate the number and/or composition of gut microbes. The goal of prebiotic consumption is to restore symbiosis and thereby confer health benefits to the host. There is convincing evidence that prebiotics can reduce adiposity and improve metabolic health in preclinical rodent models. Furthermore, there are several clinical trials in adult humans highlighting metabolic and appetite‐regulating benefits of prebiotics. In paediatric obesity, however, there are very limited data regarding the potential role of prebiotics as a dietary intervention for obesity management. As the prevalence of paediatric obesity and obesity‐associated comorbidities increases globally, interventions that target the progression of obesity from an early age are essential in slowing the obesity epidemic. This review emphasizes the need for further research assessing the role of prebiotics, particularly as an intervention in effectively managing paediatric obesity.